Perceived Acceptability of Technology Modalities for the Provision of Universal Child and Family Health Nursing Support in the First 6-8 Months After Birth: Cross-Sectional Study - Tessa Delaney; Jacklyn K Jackson; Alison L Brown; Christophe Lecathelinais; Luke Wolfenden; Nayerra Hudson; Sarah Young; Daniel Groombridge; Jessica Pinfold; Paul David Craven; Sinead Redman; John Wiggers; et al. (JMIR Publications, 2024)
BackgroundChild and Family Health Nursing (CFHN) services provide universal care to families during the first 2000 days (conception: 5 years) to support optimal health and developmental outcomes of children in New South Wales, Australia. The use of technology represents a promising means to encourage family engagement with CFHN services and enable universal access to evidenced-based age and stage information. Currently, there is little evidence exploring the acceptability of various models of technology-based support provided during the first 2000 days, as well as the maternal characteristics that may influence this. ObjectiveThis study aims to describe (1) the acceptability of technology-based models of CFHN support to families in the first 6 months, and (2) the association between the acceptability of technology-based support and maternal characteristics. MethodsA cross-sectional survey was undertaken between September and November 2021 with women who were 6-8 months post partum within the Hunter New England Local Health District of New South Wales, Australia. Survey questions collected information on maternal demographics and pregnancy characteristics, perceived stress, access to CFHN services, as well as preferences and acceptability of technology-based support. Descriptive statistics were used to describe the characteristics of the sample, the proportion of women accessing CFHN services, maternal acceptability of technology-based support from CFHN services, and the appropriateness of timing of support. Multivariable logistic regression models were conducted to assess the association between maternal characteristics and the acceptability of technology-based CFHN support. ResultsA total of 365 women participated in the study, most were 25 to 34 years old (n=242, 68%), had completed tertiary level education or higher (n=250, 71%), and were employed or on maternity leave (n=280, 78%). Almost all (n=305, 89%) women reported accessing CFHN services in the first 6 months following their child's birth. The majority of women (n=282-315, 82%-92%) "strongly agreed or agreed" that receiving information from CFHN via technology would be acceptable, and most (n=308) women "strongly agreed or agreed" with being provided information on a variety of relevant health topics. Acceptability of receiving information via websites was significantly associated with maternal employment status (P=.01). The acceptability of receiving support via telephone and email was significantly associated with maternal education level (adjusted odds ratio 2.64, 95% CI 1.07-6.51; P=.03 and adjusted odds ratio 2.90, 95% CI 1.20-7.00; P=.02, respectively). Maternal age was also associated with the acceptability of email support (P=.04). ConclusionsTechnology-based CFHN support is generally acceptable to mothers. Maternal characteristics, including employment status, education level, and age, were found to modify the acceptability of specific technology modalities. The findings of this research should be considered when designing technology-based solutions to providing universal age and stage child health and developmental support for families during the first 2000 days.